Rural Energy and Household Forest Values under Varying Management Regimes 2009. - Damte, Abebe (Environment for Development Initiative, 2020)
The study on Rural Energy and Household Forest Values under Varying Management Regimes was conducted in Ethiopia. The general objective of this survey is to study household behavior regarding sustainable land use. Households were selected from the main four regions of Ethiopia (Amhara, Oromia, SNNP, and Tigray) in 2009. The data was generated by researchers at the Ethiopian Development Research Institute and Gothenburg University.

All the datasets are in Stata format. Each data file attached consists of datasets of each section in the questionnaire.

The study on Rural Energy and Household Forest Values under Varying Management Regimes was conducted in Ethiopia. The general objective of this survey is to study household behavior regarding sustainable land use. Households were selected from the main four regions of Ethiopia (Amhara, Oromia, SNNP, and Tigray) in 2009. The data was generated by researchers at the Ethiopian Development Research Institute and Gothenburg University.

All the datasets are in Stata format. Each data file attached consists of datasets of each section in the questionnaire.
Rural Energy and Household Forest Values under Varying Management Regimes 2009
Keywords: forest management; skogsskötsel; Ethiopia; Etiopien; Agricultural and aquaculture facilities; Jordbruks- och vattenbruksanläggningar; Area management/restriction/regulation zones and reporting units; Områden med särskild förvaltning/begränsningar/reglering samt enheter för rapportering; Land cover; Landtäcke; rural energy; landsbygdsenergi; Economic systems and development; Ekonomiska system och ekonomisk utveckling; Land use and planning; Markanvändning och planering; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Economics; Nationalekonomi; Economy; Ekonomi; Environment; Miljö